A study on factors that influence organization commitment among employees at corporate office Kulim (M) Berhad / Nurhafizah Mohd Dahwam and Suraidah A Rahman - Mohd Dahwam, Nurhafizah; A Rahman, Suraidah (Faculty of Business and Management, 2014)
Changes are an ongoing-challenges faced by organization to be overcome ahead of the competitors to ensure companies gain competitive advantages. In other words, it is common place for firms to face changes both internal and external the company has to adapt to these changes. Recently, organizations need to improve their competitive advantages as to maximize the achievement from the needed changes of transformation process in order to compete with competitors. Therefore, reaching optimum productivity is the most considerable aim of each organization and it depend on human force as to plays a significant role in changing the level of productivity to ensure that organization can perform well and achieving competitive advantages. However, in today competitive world, organization cannot perform well unless the employees in such organization are committed and work effectively as a team’s in organization. It good to have a faithful employee’s who do their job task independently but in our challenging world today, employees have to work together as a team’s and have to prove that they are worth being part of these organization due to want to be half of successful organization that provide a good income and opportunities of growth and development to them (Mohamed Madi; Dr. Ismael Abu-Jarad; Ali H. M. Alqahtani, 2012). In addition, to stay be competitive, organization itself need to maintain their worker to stay and remain work with them and willingly to support organization without need to change one’s loyalty to other organization that offer more than what organization provide to them especially those worker that have an special skill or abilities. This is because changes in our life today might change the nature of work and necessity of worker in term of work environment, salary and compensation and job satisfaction that organization need to paid more attention to that issues. Meanwhile, the dissatisfaction among a special worker to organization might make them leave company and go to other company that offered more to them. On the other hand, if organization provide them with enough necessity that worker need as to keep they stay working, they will stay loyalty and committed to give all of effort to help organization become success and able to face with changes while competing with other organization. Thus, feel of loyalty and commitment to organization are important to ensure that organization might perform well, keep productive and able to stand in a line together with a successful organization in the world. According to Natalia Sarkisian, Marcie Pitt-Catsouphes, Rucha Bhate, Jungui Lee and Rene Carapinha (2011) stated that organizational commitment among respondents at the worksite in the United States does not significantly differ from the organizational commitment of employees in other country. About 83% of respondents at the worksites in the United States moderately to strongly agree that they are willing to work harder that they have to in order to help their organization succeed while 77.3% of respondents moderately to strongly agree that they feel proud to be working for their organization. Organization commitment is an important area of study to many researchers and organization because the outcome of this behavior or value may help to determine many works related interaction of the employees. It is related to the employee’s desire to stay continue working with the particular organization. Thus, both of researcher and practitioners are so keen and interested to understand the factors that may influence an employee’s decision to stay or leave the organization (Muhiniswari Govindasamy, 2009). From previous studies, there are many factors that may influence organizational commitment such as demographic, leadership, salary and compensation, job satisfaction, training and development, job security,